2001
DOI: 10.1162/10464880152474619
|View full text |Cite
|
Sign up to set email alerts
|

Architecture and Electronic Media

Abstract: These reflections on the effect of computers and computer software on teaching are based on four years of focused studio programs and course work at Rensselaer that followed the establishment of a post‐professional degree in Informatics and Architecture, and the development of a highly equipped electronic studio. They also develop some of the concerns I raised on being named Topaz Laureate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…For example, it has been demonstrated that when examining realistic visual simulations, viewers still find it difficult to accurately assess significant variations to the scale of recognizable elements (Lange 2001;Watzek and Ellsworth 1994). While these variations may slip harmlessly past the viewer of an image, they risk serious implications, if and when they come to be actualized in the corporeal landscape (Lange 2011;Balfour 2001). Even where no deception is intended, the constructed design rarely approximates the image that was initially presented as its accurate simulation (Rekittke and Paar 2009;Appleyard 1992).…”
Section: Technology: Future Deceptionmentioning
confidence: 99%
“…For example, it has been demonstrated that when examining realistic visual simulations, viewers still find it difficult to accurately assess significant variations to the scale of recognizable elements (Lange 2001;Watzek and Ellsworth 1994). While these variations may slip harmlessly past the viewer of an image, they risk serious implications, if and when they come to be actualized in the corporeal landscape (Lange 2011;Balfour 2001). Even where no deception is intended, the constructed design rarely approximates the image that was initially presented as its accurate simulation (Rekittke and Paar 2009;Appleyard 1992).…”
Section: Technology: Future Deceptionmentioning
confidence: 99%
“…They give the user remarkable confidence and a sense of fulfillment, so much so that the desire to build is potentially diminished. 1 Furthermore, Alvaro Siza observed that architects don't invent anything; they transform reality (Frampton,p. 24).…”
Section: Characterizationmentioning
confidence: 99%
“…In one school, studios are firlly netrrorked along with multimedia facilities, 3D scanning, rapid prototyplng, video editing and other capabilities (Balfour 2001). This school has also embarked on a program to equip every student with a laptop whilst providing network connections for all students in all major classrooms (Balfour 2001). In another school, due to limited resources, faculty were trying to extend creativiry (n a foundation year design snrdio) by using hybrid media (computers along with sketching and physical modelling techniques) (Moloney 1999).…”
Section: Digital Technology and Architectural Educationmentioning
confidence: 99%
“…Technology is intoxicating. Balfour (2001) argues that electronic /drgrtulmedia makes designing "an internalised, constrained and virtual experience in which the creative relationship to the tools and information held within the machine seem to be more stimulating and to hold more promise', than the reality of architecture with its extern4 diverse and physical stimuli @alfour 2001).In rhe experience of rhe pre-electronic srudio these stimuli would be historical, technical' environmental, social and phenomenal. creating rich imaginative environments that are not well connected to building real projects invariably produces graduates insufficiendy prepared for employment, further removing the academy fiom practice and from building (Cuff 2001).…”
Section: A Teaching Toolmentioning
confidence: 99%